Pemanfaatan Pestisida Nabati Ekstrak Daun Pepaya sebagai Pengendalian Ramah Lingkungan dalam Mendukung Ketahanan Pangan Berkelanjutan - Andira, Shaqila Mazaya; Wibowo, Mirza Cahyo; Carissa, Savvy Prissy Amellia; Safitri, Novia Wulan; Murtafi’ah, Roudotul; Jingga, Navisya Putri; Anjani, Rindi Dewi; Khoirunisak, Novita; Hermawan, Raditya; Romadhon, Noval Ihsan; Sukoco, Sampir Andrean (Abdimas Indonesian Journal, 2025)
This community service program addresses the critical role of food security in national development, acknowledging that agricultural productivity is often challenged by pests and diseases. While chemical pesticides are commonly used for pest control, their long-term application leads to negative environmental impacts, including increased pest resistance and harmful residues on food products. Therefore, there is a clear need for environmentally friendly, easy-to-use, and safe alternative pest control methods for household scale application. This initiative focuses on the potential of papaya leaf extract (Carica papaya L.) as a natural pesticide due to its bioactive compounds like papain, alkaloids, saponins, flavonoids, and tannins, which possess insecticidal and antimicrobial properties. The program employed a participatory educational approach in Dukuhmencek Village, involving community members, particularly active women farmers. Activities included socialization on the dangers of chemical pesticides and the benefits of natural alternatives, demonstrations of simple papaya leaf extract preparation, distribution of the natural pesticide, and guidance on its application in home gardens. Primary data was collected through interviews and observations to understand community perceptions, knowledge, and needs regarding eco-friendly pest control. The results showed that the application of papaya leaf extract effectively controlled pests like caterpillars and aphids, leading to healthier plants and reduced leaf damage. This successful implementation fostered community confidence in natural pesticides as a reliable, long-term solution, promoting environmental sustainability and reducing reliance on synthetic chemicals. The program not only enhanced technical skills but also contributed to community self-reliance and strengthened food security.